All Days 2003
DOI: 10.2118/84848-ms
|View full text |Cite
|
Sign up to set email alerts
|

Forty Years of Steam Injection in California – The Evolution of Heat Management

Abstract: TX 75083-3836 U.S.A., fax 01-972-952-9435. AbstractSteam injection EOR began in California forty years ago, and has been highly successful.As a consequence, California's thermal recovery operations represent a leading source of EOR production in the world.The understanding of most early thermal recovery operators was limited to the concept of "heat reduces heavy oil viscosity, and reduced viscosity means more production." Steam injection was attempted in almost any reservoir having viscous oil with little appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Steam injection began approximately 5 decades ago. Mene Grande and Tia Juana field in Venezuela [40,41] and Yorba Linda and Kern River fields in California [42] are good examples of steam injection projects over four decades. Some examples of recent steam injection projects reported in the literature are the steamfloods in the Crude E Field in Trinidad [43], Schoonebeek oil field in Netherlands [44] and Alto do Rodrigues in Brazil [45].…”
Section: Thermal Methodsmentioning
confidence: 99%
“…Steam injection began approximately 5 decades ago. Mene Grande and Tia Juana field in Venezuela [40,41] and Yorba Linda and Kern River fields in California [42] are good examples of steam injection projects over four decades. Some examples of recent steam injection projects reported in the literature are the steamfloods in the Crude E Field in Trinidad [43], Schoonebeek oil field in Netherlands [44] and Alto do Rodrigues in Brazil [45].…”
Section: Thermal Methodsmentioning
confidence: 99%
“…Its recovery mechanisms are majorly comprised of oil viscosity reduction, steam distillation, thermal expansion, rock compaction, and solution gas driving, , which were documented in simulation studies. ,, A CSS process is suitable for reservoirs with a thickness of over 10 m, oil saturation of over 40%, porosity of over 30%, and a depth of at least 300 m. , Its applications have been highly concentrated in Brazil, Canada, China, Russia, United States, and Venezuela . Many CSS fields have been successfully operated for over five decades, for example, Cold Lake in Canada, Mene Grande and Tia Juana fields in Venezuela, , and Yorba Linda and Kern River fields in California . A steam to oil ratio (SOR) for CSS in initial cycles is around 2 but increases to 5 in later cycles.…”
Section: Cyclic Steam Stimulation (Css)mentioning
confidence: 99%
“…Early simulation work by Crookston in 1979 showed that adding an underlying water layer helped steam injection . But in most of the reservoirs operated by CSS, continuous bottom water layers were not observed. Briggs in 1989 developed a thermal simulator with the presence of fractures, which solved the steam injectivity issue . Other simulation studies by Duerksen et al (1984) and Dietrich (1986) applied rock compressibility of one or two orders of magnitude larger than a lab measured value, called a “sponge model”.…”
Section: Cyclic Steam Stimulation (Css)mentioning
confidence: 99%
“…Thermal recovery is a common method to improve heavy oil recovery. However, due to the energyintensive emission of a large amount of carbon dioxide, the heavy oil thermal recovery was severely restricted by many countries (De Haan and Van Lookeren, 1969;Hanzlik and Mims, 2003;Ramlal, 2004;Ernandez, 2009). Thus, method of cold recovery of heavy oil has been used in many oil fields.…”
Section: Introductionmentioning
confidence: 99%